Tetracyclines, a promise for neuropsychiatric disorders: from adjunctive therapy to the discovery of new targets for rational drug design in psychiatry. Issue 2 (15th February 2021) - Chaves Filho, Adriano José Maia; Mottin, Melina; Soares, Michele Verde-Ramo; Jucá, Paloma Marinho; Andrade, Carolina Horta; Macedo, Danielle S.
Abstract : Major mental disorders, such as schizophrenia, bipolar disorder, and major depressive disorder, represent the leading cause of disability worldwide. Nevertheless, the current pharmacotherapy has several limitations, and a large portion of patients do not respond appropriately to it or remain with disabling symptoms overtime. Traditionally, pharmacological interventions for psychiatric disorders modulate dysfunctional neurotransmitter systems. In the last decades, compelling evidence has advocated for chronic inflammatory mechanisms underlying these disorders. Therefore, the repurposing of anti-inflammatory agents has emerged as an attractive therapeutic tool for mental disorders. Minocycline (MINO) and doxycycline (DOXY) are semisynthetic second-generation tetracyclines with neuroprotective and anti-inflammatory properties. More recently, the most promising results obtained in clinical trials using tetracyclines for major psychiatric disorders were for schizophrenia. In a reverse translational approach, tetracyclines inhibit microglial reactivity and toxic inflammation by mechanisms related to the inhibition of nuclear factor kappa B signaling, cyclooxygenase 2, and matrix metalloproteinases. However, the molecular mechanism underlying the effects of these tetracyclines is not fully understood. Therefore, the present review sought to summarize the latest findings of MINO and DOXY use for major psychiatric disorders and present the possible targets to their molecular and behavioral effects. In conclusion, tetracyclines hold great promise as (ready-to-use) agents for being used as adjunctive therapy for human neuropsychiatric disorders. Hence, the understanding of their molecular mechanisms may contribute to the discovery of new targets for the rational drug design of novel psychoactive agents.